Philosophical views on the development of ideas about consciousness - Xaqberdiev Alpomish Komil o‘g‘li (Zien Journals, 2021)
In the new era, R. Descartes (1596-1650) equated consciousness with thinking, separated it from the more general concept of "psyche" and considered consciousness as an independent, free-thinking substance, as opposed to other adjacent - large-scale, non-thinking, material substance. ydi. This philosophical approach, called dualism, later paved the way for the emergence of two opposing approaches to understanding the nature of consciousness.
Keywords: new; dualism; emergence; paved